Experimental investigation of the novel design for shock proof hard disk drive development - Koh, Kwang Liang. (2009)
The project is to improve on the shock response of an existing hard disk drive, the 3.5” Cheetah Hard Disk Drive (HDD). The focus of the project is to improve the shock response of the HDD by novel designs of three key components; i.e. suspension flexure, base plate and top cover. Using SolidWorks and Pro/E to create the computer-aideddesign (CAD) model of these original HDD components, modification and novel designs can be done based on analysis results. ANSYS Workbench will be used to run analysis at the initial designing stage at component level before the chosen designs are incorporated into the full finite element (FE) model of the HDD. ANSYS Workbench analyses include modal analysis, steady structural analysis and harmonic response analysis. A modal analysis determines the vibration characteristics (natural frequencies and mode shapes) of a structural or a machine component. A steady structural analysis determines the steady displacements, stresses and strains in structural components caused by accelerations loads equivalent to the shock loads. In a structural system, dynamic cyclic load will produce a sustained cyclic or harmonic response. Harmonic response analysis results are used to determine the response of a linear structure to loads in frequency domain.